2005
DOI: 10.1073/pnas.0507718102
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evidence for arterial repair in atherosclerosis

Abstract: Atherosclerosis is a chronic inflammatory process and progresses through characteristic morphologic stages. We have shown previously that chronically injecting bone-marrow-derived vascular progenitor cells can effect arterial repair. This repair capacity depends on the age of the injected marrow cells, suggesting a progressive decline in progenitor cell function. We hypothesized that the progression of atherosclerosis coincides with the deteriorating repair capacity of the bone marrow. Here, we ascribe pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
73
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 81 publications
(76 citation statements)
references
References 40 publications
3
73
0
Order By: Relevance
“…We also were able to define a molecular signature that corresponds to efficient repair of the arterial wall (11). Genes that constitute this pool often have to do with cellular functions that are important for stem cells.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…We also were able to define a molecular signature that corresponds to efficient repair of the arterial wall (11). Genes that constitute this pool often have to do with cellular functions that are important for stem cells.…”
mentioning
confidence: 99%
“…However, a couple of years ago, we showed for the first time that atherosclerosis is not simply the result of direct injury to the arterial wall, but instead the consequence of such injury in a context in which the intrinsic repair process for the arterial wall is no longer fully functional (6,7). Our laboratory (11) and other groups of investigators (5) have shown that arterial repair is triggered by arterial injury, which, in turn, provokes a local inflammatory reaction (7) (Fig. 1).…”
mentioning
confidence: 99%
See 3 more Smart Citations